Analysis of the quadratic term in the backscattering transformation - Beltita, Ingrid; Melin, Anders (Mathematica Scandinavica, 2009)
The quadratic term in the Taylor expansion at the origin of the backscattering transformation in odd dimensions n3 gives rise to a symmetric bilinear operator B_2 on C_0^∞(R^n)× C_0^∞(R^n). In this paper we prove that B_2 extends to certain Sobolev spaces with weights and show that it improves both regularity and decay.